Das políticas nacionais aos planos municipais: avanço da política pública de assistência social em metrópoles - estudo das cidades do Rio de Janeiro e de São Paulo - Alchorne, Sindely Chahim de Avellar (2012)
The present search makes an analysis of the politics of Social Assistance in Brazil from 1993 to 2012, of LOAS - Organic Law of Social Assistance to present days, from the reality of two big cities Rio de Janeiro and São Paulo. It passes the trajetory of national norms: National Politics of Social Assistance (PNAS) Basic Operational norms of Social Assistance (NOB).The exam of norms from the reality of the two biggest cities of the country: Rio de Janeiro ans São Paulo let to create questions about the operation of the politics of social assistance from the Municipal Secretaries responsible for this politics. It also gives importance to Municipal Plans of Social Assistance and Work Relatories, like instruments used in these norms and that make sure (or it must make sure) the social control and the popular participation. There is a cronic question in politics of social assistance: no systematization and because of this no knowledge of its historic trajetory. There are no studies, analysis, searches and documents about a recent history in the country. This way the search goes with the problem of analmost absent history of politics of social assistance in the country. I defend the thesis that the form of SUAS (the only system of Social Assistance) has the support of a trajetory of fights, confronts and conquers, that can be seen in the two big metropolitan centers analysed: Rio de Janeiro and São Paulo. National Fights do not take off local fights, on the contrary, they are on line and they give force in the search of the aim